Effects of Housing Systems on Some Fatty Acid Contents of Hen´ s Eggs - SEKEROGLU, A.; SARICA, M.; DEMIR, E.; ULUTAS, Z. (Asian Journal of Chemistry, 2010)
This research was carried out to investigate the effects of housing systems (deep litter, free range and cage systems) on fatty acids composition of eggs obtained from brown layer strain of ATAK (GxSx). In deep litter, free range and cage systems of the egg contain palmitic fatty acids, were 24.14, 24.30 and 34.2 %; stearic fatty acids were 5.21, 5.34 and 4.56 %; palmitoleic fatty acids were 4.17, 3.45 and 3.62 %; oleic fatty acids were 46.57, 47.28 and 46.06 %; linoleic fatty acids were 17.90, 16.86 and 20.01 % in three conditions, respectively. In conclusion, more detailed studies are necessary to show the differences and advantages of main applicable poultry housing systems.